The Impact of Competence and HR Quality on Organizational Performance with Motivation as an Intervening Variable at Bank Indonesia - RUSIANTO, Beni; KHASMIR, Khasmir (International Journal of Environmental, Sustainability, and Social Science, 2023)
This research aims to determine the effects of competence, human resource quality, and motivation on the organizational performance at Bank Indonesia. It seeks to understand the impact of competence and human resource quality on motivation and examine the influence of competence and human resource quality on organizational performance at Bank Indonesia, with motivation as a moderating variable. This study employs Partial Least Square analysis using the SmartPLS. The findings suggest that no significant relationship exists between competence and organizational performance at Bank Indonesia. HR quality has a significant positive effect on organizational performance at Bank Indonesia. There is insufficient evidence to assert a significant relationship between competence and motivation at Bank Indonesia. HR quality has a powerful positive influence on motivation at Bank Indonesia. Motivation significantly and positively affects organizational performance at Bank Indonesia. No significant measurable effect was found between competence and organizational performance through motivation in this sample at Bank Indonesia. However, a significant measurable effect was observed between HR quality and organizational performance through motivation in this sample at Bank Indonesia.